Language and Context in Inter-Cultural Communication - Abushihab, Dr. Ibrahim (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The text is considered as a final product which exists in the mind as the result of a mental activity. It is a unit of human action, interaction, communication and cognition which are based on the context. Background knowledge of the social context and its cultural norms and the power of contextual inference help in finding the particular meaning of the text. Context is an idealized abstraction of the required meaning from the communicative situation whereas contextualization, as defined by Brelsford and Rogers (2008:1) is international effort to extend learning beyond the classroom into relevant contexts in the real world, and it also entails bringing realities of those extra academic comments into the classroom. Students who belong to a different culture often find themselves out of touch with the content of the topic being taught. Context and contextualization are essential in solving such issues.